Ultrafine particles and nitrogen oxides generated by gas and electric cooking. Issue 8 (1st August 2001) - Dennekamp, M; Howarth, S; Dick, C A J; Cherrie, J W; Donaldson, K; Seaton, A
Abstract : OBJECTIVES: To measure the concentrations of particles less than 100 nm diameter and of oxides of nitrogen generated by cooking with gas and electricity, to comment on possible hazards to health in poorly ventilated kitchens. METHODS: Experiments with gas and electric rings, grills, and ovens were used to compare different cooking procedures. Nitrogen oxides (NOx ) were measured by a chemiluminescent ML9841A NOx analyser. A TSI 3934 scanning mobility particle sizer was used to measure average number concentration and size distribution of aerosols in the size range 10–500 nm. RESULTS: High concentrations of particles are generated by gas combustion, by frying, and by cooking of fatty foods. Electric rings and grills may also generate particles from their surfaces. In experiments where gas burning was the most important source of particles, most particles were in the size range 15–40 nm. When bacon was fried on the gas or electric rings the particles were of larger diameter, in the size range 50–100 nm. The smaller particles generated during experiments grew in size with time because of coagulation. Substantial concentrations of NOX were generated during cooking on gas; four rings for 15 minutes produced 5 minute peaks of about 1000 ppb nitrogen dioxide and about 2000 ppb nitric oxide. CONCLUSIONS: Cooking in a poorly ventilated kitchen may give rise to potentially toxic concentrations of numbers of particles. Very high concentrations of oxides of nitrogen may also be generated by gas cooking, and with no extraction and poor ventilation, may reach concentrations at which adverse health effects may be expected. Although respiratory effects of exposure to NOx might be anticipated, recent epidemiology suggests that cardiac effects cannot be excluded, and further investigation of this is desirable.